Physical Properties and Sensory Evaluation of Agarwood Leaves Extract Powder Through Enzyme Treatment - Mohd Jamiran, Nur Fathihah; A. Talip, Balkis (Enhanced Knowledge in Sciences and Technology, 2025)
Enzymes mostly could act on molecular structures allowing for the generation of specific compounds, which is particularly beneficial in the food industry and flavour is a key determinant of food quality which is influenced by enzymes that can enhance undesirable tastes. This study aims to focusing on enhancing its flavour through bromelain enzymatic treatment and food colourants based on the physical properties. Besides that, agarwood leaves extract was extracted using the decoction method. The untreated agarwood leaves extract was subjected to a water bath at 50°C for 5 minutes and followed by treated agarwood leaves extract was water bath at 50°C for 3 hours to ensure the enzyme operates at peak efficiency, promoting the desired reactions without denaturing the enzyme. The extract was then spray-dried at temperatures ranging from 180°C to 200°C, with a feed rate of 10-20 rpm. Bromelain was used at a concentration of 18%, diluted with 1000 mL of distilled water. The treated powder exhibited improved flavour with reduced bitterness and enhanced sweetness. Sensory evaluation confirmed a preference for the enzyme-treated sample in which formulation 2, the treated with bromelain was preferred for its improved sweetness and appearance. Statistical analysis showed significant differences between treated and untreated formulations in acceptance based on the sensory evaluation which is the superscript letter was denoted as significance value (p